VISUAL COMMUNICATION AND INFORMATION DESIGN IN PUBLIC HEALTH CAMPAIGNS - Tungaskar, Ganesh Rohidas; Kadam, Yugantara Ramesh; Sinha, Garima; T. Puhazhendhi; Pawar, Nilesh M; Sairise, Raju M (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Communication skills are critical in effective public health campaigns, particularly in the delivery of complex health information in a manner that is easy to understand, engage and to be reached by the various populations. Information design and visual communication is particularly important to influence the perceptions, interpretations, and reactions of the audience on the health messages. Over the last few years, there has been a rise in the use of visual data like infographics, pictograms, data visualizations, and interactive media in the dissemination of important information concerning disease prevention, vaccination, hygiene, and lifestyle modifications by governmental bodies in the area of public health. The COVID-19 pandemic showed the relevance of effective visual communication in regulating the behavior of the population and decreasing misinformation. Nevertheless, regardless of the general use of visual components in health campaigns, there are still concerns of readability, cultural inclusiveness, usability, and information overload. The present research paper will explore how visual communication and information design can be used to make the public health campaigns more effective. The research presents the literature on the field of health communication design, assesses the most popular visual techniques, and determines the weaknesses of the existing practices. The traditional text-based communication and visual-centric health messaging are comparatively analyzed to prove the advantages in the understanding, memory, and the involvement of viewers. It is on the basis of these findings that a structured Visual Health Communication Framework (VHCF) is suggested in the paper, which is a combination of a design principle, behavioral psychology, and digital media technologies. The framework will enhance clarity of messages, understanding of the audience, and their involvement in the public health programs. The paper concludes that strategic visual design is important in increasing the reach and effectiveness of a public health campaign. A combination of data visualization, culturally mindful imagery, and user-friendly design principles can help the organization of the field of public health to develop more effective communication approaches. This research can be of great use to designers, policy-makers, and health care providers who can enhance health literacy and favorable health behaviors by using visual media.